THE RELATIONSHIP BETWEEN NUMBER SENSE AND METACOGNITION - (:unkn) unknown (My University, 2018)
It is increasingly recognized that higher order thinking skills are necessary to meet the challengesin the 21st century. Because in order to reach information, individuals need to have skills such asproblem solving, organizing their own learning, transferring the acquired knowledge to newsituations, reasoning, critical thinking, developing creative and original strategies, flexible thinking,estimation and mental computation. In recent years, these skills are expressed by number senseand metacognition. In literature review, there are several research findings that there is asignificant relationship between mathematics achievement with number sense and metacognition.These findings suggest a relationship between these two concepts. Starting from this point thepurpose of this study is to explain the concepts of metacognition and number sense and to examinethe relationship between these two concepts. This study was designed in the form of a literaturereview based on synthesizing the data. As a result of the theoretical reviews, it was concluded thatnumber sense and metacognition are supports both mathematics achievement and themathematical thinking. Number sense and metacognition are skills based on flexible thinking.
SAYI HİSSİ VE ÜSTBİLİŞ İLİŞKİSİ
Keywords: Arkeoloji; Sanat; Coğrafya; Tarih; Dil ve Dil Bilim; Hukuk; Müzik; Felsefe; Sosyoloji